Peningkatan Keterampilan Prajurit TNI-AL Dalam Mempersiapkan Purna Tugas Melalui Ketrampilan Pengolahan Limbah Organik - Yektiningsih, Endang; Siswanto; Yudha Adytama, Ahmad; Queen Tsamara, Vienes; Fahrezi Taufiq, Fariz; Pricillia Siahaan, Ellecia (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
AbstractThe focus of the Indonesian National Army's work while still active is to maintain regional security, so preparation is needed before retirement by having skills that can be used for productive activities during their retirement. Indonesian Navy soldiers who serve in the Command Education (KOLAT) Armada-II, Semampir District, Surabaya, are mostly around 50-56 years old with strong and productive physical conditions. Therefore, it is necessary to strive for activities to improve skills that have the potential to become new businesses. The activities carried out are processing organic waste into compost and animal feed. The implementation method consists of counseling, training, discussion and evaluation of activity results. The results of the activities show that there is an increase in knowledge and skills regarding the method of processing organic waste into organic fertilizer and animal feed as well as the growth of interest in making it a new business.